Tanggung Jawab Hukum Pelaku Usaha Jasa Transportasi Dalam Memberikan Pelayanan Maksimal dan Kompensasi Kepada Konsumen - Insan Tajali Nur (Fakultas Hukum Universitas Mulawarman, 2006)
The services from any transportation companys sometimes have a negative implication to consumer. Sometimes its caused by the companys itself such as they always run against time to reach an huge profit, human resource weaknesses, the limited facilities, lack of management coordination. As a result, it can affecting a loss of time, energy or financial by consumer. In that case, transportation campanys can be told “wanprestasi”. In this situation consumer can claim an indemnation and compensation in the form of replacement of goods and/or service if which is accepted disagree with agreement according to Article 4 point h Undang-undang Perlindungan Konsumen. Key words: perlindungan konsumen (protection of consumerism), konsumen (consumer), pelaku usaha jasa transportasi (transportation services companys)